VD_FINDINFO Décision / 2015 / 892 vom 3. Dezember 2015 - VD Tribunal cantonal (2015)
NON-LIEU, ACCIDENT DE LA CIRCULATION, PRIORITÉCIRCULATION, DILIGENCE | 36 al. 1 LCR, 36 al. 2 LCR, 3 al. 1 OCR, 319 CPP (CH)